Use of central venous access devices and its complications in neonates - Gupta, Vivek; Jain, Gitanjali; Gupta, Rakesh; Mallick, Achinta Kr; Narula, Gaurav (Indian Journal of Child Health, 2018)
Background: Intravenous therapy is a major component in the health care and appropriate research-based knowledge is essential to ensure positive patient outcomes. Objective: The objective of the study was to study the use of Central Venous Access Devices (CVADs) and their complications in neonates in routine practice. Methods: A prospective observational study was conducted at a tertiary care neonatal intensive care unit (NICU) on 40 newborns. CVADs were inserted in neonates, who had been anticipated to have intravenous access for >7 days. CVADs used in the study included Peripherally Inserted Central Catheters (PICCs) and umbilical venous catheters. CVADs were inserted under strict aseptic precautions as per international guidelines, and maintenance protocols followed. Monitoring for complications was done daily. Central Line Associated Blood Stream Infection (CLABSI) was established by a combination of suggestive clinical signs and blood culture reports as per Centre for Disease Control and prevention definition. Results: Extremely low birth weight neonates contributed 40% of the patients. PICC insertions formed the 85% of the devices used. Basilic vein was the preferred site of the insertion in almost one-half of the patients. 80% of the PICCs in neonates were used to administer total parenteral nutrition. CLABSI was the most common complication occurring at a rate of 7.5/1000 catheter days. Other complications were occlusion, suspected infection, accidental displacement, and thromboembolism. Conclusion: Central venous catheterization is a safe and efficient procedure with minimal complication in neonates. This study emphasizes its use whenever prolonged intravenous access requirement is expected.